Abscisic acid induced changes in production of primary and secondary metabolites, photosynthetic capacity, antioxidant capability, antioxidant enzymes and lipoxygenase inhibitory activity of Orthosiphon stamineus benth - Ibrahim, Mohd Hafiz; Jaafar, Hawa Z. E. (MDPI, 2013)
An experiment was conducted to investigate and distinguish the relationships in the production of total phenolics, total flavonoids, soluble sugars, H2O2, O2 -, phenylalanine ammonia lyase (PAL) activity, leaf gas exchange, antioxidant activity, antioxidant enzyme activity [ascorbate peroxidase (APX), catalase (CAT), superoxide dismutase (SOD) and Lipoxygenase inhibitory activity (LOX)] under four levels of foliar abscisic acid (ABA) application (0, 2, 4, 6 μM) for 15 weeks in Orthosiphon stamineus Benth. It was found that the production of plant secondary metabolites, soluble sugars, antioxidant activity, PAL activity and LOX inhibitory activity was influenced by foliar application of ABA. As the concentration of ABA was increased from 0 to 6 μM the production of total phenolics, flavonoids, sucrose, H2O2, O2 -, PAL activity and LOX inhibitory activity was enhanced. It was also observed that the antioxidant capabilities (DPPH and ORAC) were increased. This was followed by increases in production of antioxidant enzymes APX, CAT and SOD. Under high application rates of ABA the net photosynthesis and stomatal conductance was found to be reduced. The production of primary and secondary metabolites displayed a significant positive relationship with H2O2 (total phenolics, r2 = 0.877; total flavonoids, r2 = 0.812; p ≤ 0.05) and O2 - (total phenolics, r2 = 0.778; total flavonoids, r2 = 0.912; p ≤ 0.05). This indicated that increased oxidative stress at high application rates of ABA, improved the production of phytochemicals.